2015
DOI: 10.1259/bjr.20140638
|View full text |Cite
|
Sign up to set email alerts
|

Does background parenchymal enhancement on MRI affect the rate of positive resection margin in breast cancer patients?

Abstract: Objective: The purpose of our study was to evaluate whether strong background parenchymal enhancement (BPE) would be a significant independent factor associated with positive resection margin in patients treated initially with breast-conserving surgery (BCS). Methods: Retrospective evaluation of breast MRI examinations of 314 patients with breast cancer was carried out. Breast cancer was histologically confirmed in all patients who underwent BCS from January 2008 to December 2010. BPE was dichotomized into wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…MR imaging is routinely used to monitor treatment response to neoadjuvant chemotherapy. Studies have suggested a correlation between various MR imaging parameters, such as baseline morphologic features, functional tumor volume, background parenchymal enhancement, and pCR in patients with HER2-positive breast cancer (23)(24)(25)(26)(27). These studies show good results, with some suggestion that MR imaging is more accurate in predicting pCR in ER-negative tumors (28).…”
Section: Discussionmentioning
confidence: 99%
“…MR imaging is routinely used to monitor treatment response to neoadjuvant chemotherapy. Studies have suggested a correlation between various MR imaging parameters, such as baseline morphologic features, functional tumor volume, background parenchymal enhancement, and pCR in patients with HER2-positive breast cancer (23)(24)(25)(26)(27). These studies show good results, with some suggestion that MR imaging is more accurate in predicting pCR in ER-negative tumors (28).…”
Section: Discussionmentioning
confidence: 99%
“…In general, a higher risk of breast cancer is reported with increased BPE (8,9,39,40,43). Patients with increased BPE have an increased risk of tumors with positive resection margins (44). More pronounced stromal enhancement surrounding the tumor is related to extensive ductal carcinoma in situ (45).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the rates of residual suspicious calcifications on post-excision mammography and residual malignancy in our study was higher than those previously reported. 12,25,26 However, excisions were performed in our study for pathologic confirmation and not for complete tumor removal.…”
Section: Gyeongmin Park Et Almentioning
confidence: 98%